Two new myrmecophilous species of the genus Petalomium (Acari: Pygmephoroidea: Neopygmephoridae) - Khaustov, Alexander A. (Zootaxa, 2015)
Two new myrmecophilous species of the genus Petalomium Cross, 1965 (Acari: Pygmephoroidea: Neopygmephoridae), P. crossi sp. nov. and P. reductus sp. nov. are described from ants Myrmicaria distincta Santschi, 1925 (Hymenoptera: Formicidae: Myrmicinae) in Ethiopia. The presence and shape of the postpalpal setae in species of the genus Petalomium are discussed.